Análisis Jurídico de la adopción desde la concepción en resultado de embarazo por violación. - Jaramillo Cuenca, María Laura (2023)
This work of Curricular Integration is entitled: legal analysis of adoption from conception in result of pregnancy from rape. has as its main objective to establish in Ecuadorian society a legal framework that allows the legalization of adoption from conception in cases of pregnancy from rape, as well as based on the existing regulations applicable to the cases in question. The need to develop and implement a process of adoption from conception when the pregnancy is the result of rape is important since there are cases in which women who have been victims of rape seek an alternative that does not necessarily lead to an abortion, limiting the most important protected legal right mentioned in our supreme law, which is life. For the development of this research of juridical relevance, different research points were implemented, such as doctrinal, juridical and conceptual. In this way methods such as: scientific, inductive, deductive, analytical, exegetical, hermeneutic, comparative, statistical, in addition to the application of techniques such as survey and interview, for which the city of Loja is taken into consideration for the collection of opinions of law professionals, to verify the problems raised and propose the incorporation of a reform in the Code of Childhood and Adolescence. This research verifies that the figure of Adoption from Conception would guarantee women to have another alternative when they suffer a sexual aggression allowing women to make free decisions about their sexual and reproductive life. This research project seeks to discern the legal vacuum regarding the legal figure of Adoption in cases of rape, in such a way that life is guaranteed and protected as the supreme protected legal right.